Carbon-coated mesoporous silicon shell-encapsulated silicon nano-grains for high performance lithium-ion batteries anode. (15th June 2022) - Wang, Jie; Gao, Chunhui; Yang, Zhao; Zhang, Min; Li, Zhaolin; Zhao, Hailei
Abstract: Silicon is considered to be a promising anode material because of its higher theoretical specific capacity. However, the huge volume change in cycles leads to a severe pulverization of active silicon and thus rapid capacity fade. Herein, to address this issue, we report a novel hollow-structured Si/C (H–SiNS/C) nanocomposite fabricated via a simple, facile approach. In the composite, lots of tiny Si nano-grains are encapsulated by a thin mesoporous Si shell, which is further coated by a carbon layer. The mesoporous Si shell with abundant internal voids can effectively accommodate the volume changes and relieve the mechanical stress during repeated (de)lithiation processes. Besides, the carbon layer can function as the hard physical-mechanical support to further confine the internal Si shell expansion/contraction, guaranteeing the whole particle structural integrity. Moreover, the conductive framework constructed by the carbon layer favors the electrode reaction kinetics as well as the uniform volume variation of Si. As a result, the H–SiNS/C nanocomposite displays a high reversible capacity (0.1 A g −1 : ∼1670 mAh g −1 ), an excellent rate capability (2 A g −1 : >1150 mAh g −1 ) with a high average Coulombic efficiency (∼99.8%), and a superior cycling stability. Graphical abstract: Image 1 Highlights: Novel Si/C anode is synthesized via a simple, facile method. Carbon-coated Si shell with internal voids provides enough space for Si expansion. Carbon layer acts as physical-mechanical support and electron conductive network. Excellent cycling performance with high Coulombic efficiency was achieved.